Impacts of Motor Developmental Delay on the Inter-Joint Coordination Using Kinematic Synergies of Joint Angles During Infant Crawling - Li Zhang; Chun F. Deng; Yuan Liu; Lin Chen; Nong Xiao; Sheng J. Zhai; Wen S. Hou; Yu X. Chen; Xiao Y. Wu (IEEE, 2022)
Motor developmental delay (MDD) usually affects the inter-joint coordination for limb movement. However, the mechanism between the abnormal inter-joint coordination and MDD is still unclear, which poses a challenge for clinical diagnosis and motor rehabilitation of MDD in infant’s early life. This study aimed to explore whether the joint activities of limbs during infant crawling are represented with kinematic synergies of joint angles, and evaluate the impacts of MDD on the inter-joint coordination using those synergies. 20 typically developing infants, 16 infants at risk of developmental delay, 11 infants at high risk of developmental delay and 13 infants with confirmed developmental delay were recruited for self-paced crawling on hands and knees. A motion capture system was employed to trace infants’ limbs in space, and angles of shoulder, elbow, hip and knee over time were computed. Kinematic synergies were derived from joint angles using principal component analysis. Sample entropy and Spearman’s rank correlation coefficients were calculated among those synergies to evaluate the crawling complexity and the symmetry of bilateral limbs, respectively. We found that the first two synergies with different contributions to the crawling movements sufficiently represented the joint angular profiles of limbs. MDD further delayed the development of motor function for lower limbs and mainly increased the crawling complexity of joint flexion/extension to some extent, but did not obviously change the symmetry of bilateral limbs. These results suggest that the time-varying kinematic synergy of joint angles is a potential index for objectively evaluating the abnormal inter-joint coordination affected by MDD.